Avaliação de tratamento adjuvante com radioterapia associado a quimioterapia de radiossensibilização com 5FU e leucovorin em pacientes com câncer gástrico no Instituto do Câncer do Ceará no período de 2002 a 2017: estudo retrospectivo - Oliveira, Mário Vilâny Gomes Bonfim (2019)
The chemoradiotherapy (QT / RT) is one of the modalities of choice in the adjuvant treatment of gastric cancer patients, as its benefit has been demonstrated in previous studies. The purpose of this research was to evaluate, through a retrospective study, the role of 5FU and Leucovorim-associated chemoradiotherapy in patients with gastric cancer according to certain patient subgroups. Data from 81 patients diagnosed with gastric adenocarcinoma undergoing QT / RT between 2002 and 2017 were analyzed. Eighteen percent of patients developed relevant toxicities such as grade 3 and grade 4 diarrheas, followed by neutropenia with 11.1% and asthenia with 4.9%. In ten years, the amount of living people was 51%. Patients with and without lymph node involvement had a similar overall survival, regardless of the extent of the disease. Regarding the intestinal histological subtype, there was a numerically better overall (SG) survival compared to diffuse, but without statistical significance. There was a difference of benefit in SG compared to the surgical techniques employed, 68% x 49% in 10 years, in favor of the D1 technique (p=0.044). Despite the numerical difference, there was no statistical significance in favor of the tumor site or time to start treatment.